Evaluation of partial discharge localization in power transformer with weighted centroid method - Tiengthong, Thanadol; Sanguanpuak, Chanidaphar; Southisombat, Khamphoui; Promwong, Sathaporn (My University, 2019)
Partial discharge localization in power transformer is very important. A suitable evaluation method is one of the most critical part in order to find the exactly location of partial discharge. In this paper, an ultra-high frequency partial discharge localization is introduced. Weighted centroid method is one of a suitable method to evaluate the localization in partial discharge localization as well as other wireless localization system. There are many limitation of place to install the antenna in power transformer. The proper antenna placing is very important issue because improper location will affect the accuracy of partial discharge localization. The experiment of partial discharge measurement is carried out on a power transformer model from tesla power company. The purposed method used weighted centroid with received signal strength to evaluation the partial discharge in power transformer. The results show average value of received signal strength at each measurement position and the distance error of partial discharge location with weighted centroid method. The benefits of this method is useful to evaluate the partial discharge in power transformer.
Keywords: partial discharge localization; power transformer; received signal strength; UHF; weighted centroid